2020
DOI: 10.1089/met.2019.0097
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and Skeletal Muscle Adiposity Are Associated with Diabetes Independent of Visceral Adiposity in Nonobese African-Caribbean Men

Abstract: Background: Adipose tissue (AT) around and within non-AT organs (i.e., ectopic adiposity) is emerging as a strong risk factor for type 2 diabetes (T2D). Not known is whether major ectopic adiposity depots, such as hepatic, skeletal muscle, and pericardial adiposity (PAT), are associated with T2D independent of visceral adiposity (VAT). More data are particularly needed among high-risk nonobese minority populations, as the race/ethnic gap in T2D risk is greatest among nonobese. Methods: Thus, we measured severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Subcutaneous adipose tissue was determined as adipose tissue beneath the skin and superficial to the abdominal or thigh muscular fascia [26]. Visceral adipose tissue was determined as adipose tissue within the peritoneal cavity [23]. Intermuscular adipose tissue was determined as adipose tissue within the muscle fascia and between muscle fasciculi of the psoas and paraspinal muscle groups for abdominal intermuscular adipose tissue and adductor, quadriceps, and hamstring muscle groups for thigh intermuscular adipose tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Subcutaneous adipose tissue was determined as adipose tissue beneath the skin and superficial to the abdominal or thigh muscular fascia [26]. Visceral adipose tissue was determined as adipose tissue within the peritoneal cavity [23]. Intermuscular adipose tissue was determined as adipose tissue within the muscle fascia and between muscle fasciculi of the psoas and paraspinal muscle groups for abdominal intermuscular adipose tissue and adductor, quadriceps, and hamstring muscle groups for thigh intermuscular adipose tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Liver fat was analyzed using open‐source OsiriX software custom‐programmed subroutines. ( 25 ) Images at T12‐L1 were used to identify the liver below the right diaphragm corresponding to superior aspects of the right and medial lobes or hepatic segments 4a, 7, and 8 using the Couinaud system. Three regions of interest were measured within homogenous portions of the liver on each of three different CT slices, and liver attenuation was averaged from the nine total regions.…”
Section: Methodsmentioning
confidence: 99%
“…PAT volume was measured within a 45‐mm block of images spanning 15 mm above and 30 mm below the superior extent of the left main coronary artery, which includes the adipose tissue located around the epicardial coronary arteries (left main coronary, left anterior descending, right coronary, and circumflex arteries) as well as the epicardial and PAT around the coronary arteries, as previously described in detail. ( 25 , 26 )…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the Diabetes Metab J 2021;45:482-491 https://e-dmj.org Coronary Artery Risk Development in Young Adults (CAR-DIA) Study [18], among 3,170 African-American and White participants aged 43 to 55 years, reported that total abdominal IMAT was positively associated with prevalence of T2DM, even after adjustment for VAT. Moreover, the Tobago Health Study [20], among 718 African-Caribbean men aged 40 years and older, reported that a lower muscle density in the calf was associated with greater prevalence of T2DM among non-obese men, independent of VAT, and other relevant ectopic fat depots, such as hepatic and pericardial adiposity. Notably, muscle density was not associated with T2DM among obese men in this cohort of African-Caribbeans.…”
Section: Myosteatosis and Insulin Resistance And Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Thus, in the last 10 years, several well-designed, large, epidemiologic studies were able to test if the associations between myosteatosis and T2DM were independent of VAT. The majority of these newer studies have consistently reported that CT-measured IMAT [ 17 , 18 ] and muscle density [ 19 , 20 ] are associated with prevalent T2DM, independent of VAT, suggesting that metabolic impairments associated with increased myosteatosis are not simply due to increased VAT. For instance, the Osteoporotic Fractures in Men (MrOS) Study [ 17 ], among 393 nondiabetic elderly White men, found total abdominal IMAT and psoas IMAT to be positively associated with fasting HOMA‐IR, independent of VAT.…”
Section: Myosteatosis and Insulin Resistance And Type 2 Diabetes Mellitusmentioning
confidence: 99%